વિજ્ઞાન અને ટેકનોલોજી,ધોરણ-10 - (:unkn) unknown (Gujarat State Board of School Textbooks (GSEB), 2014)
The book is a Gujarati medium Science and Technology textbook for class-10.
Science and Technology, Class-10
Keywords: Gujarati; વિજ્ઞાન અને ટેકનોલોજી; ધોરણ-10; Science and Technology; Class-10; Science and Technology; Gujarati; Gujarati